2008
DOI: 10.1097/pep.0b013e31818add5d
|View full text |Cite
|
Sign up to set email alerts
|

Parent Preferences for Motor Development Education in the Neonatal Intensive Care Unit

Abstract: Parents of infants who were born preterm would benefit from education using multiple approaches. The parent education intervention developed in this study is clear and well understood by parents. Further research is needed to evaluate the efficacy of this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Parents report, however, an interest in learning about infant development and a need for information on how to support development during the transition from the neonatal intensive care unit (NICU) to home. [6][7][8] Infants and families who overcome the barriers to enrolling in EI services frequently receive low-intensity intervention, which evidence suggests has little to no lasting effect on motor and cognitive development. 3,9 Basic science and clinical evidence, however, suggest early and intense intervention is more effective than a long-term lowintensity approach at promoting neural recovery in adults and children with a variety of disabilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents report, however, an interest in learning about infant development and a need for information on how to support development during the transition from the neonatal intensive care unit (NICU) to home. [6][7][8] Infants and families who overcome the barriers to enrolling in EI services frequently receive low-intensity intervention, which evidence suggests has little to no lasting effect on motor and cognitive development. 3,9 Basic science and clinical evidence, however, suggest early and intense intervention is more effective than a long-term lowintensity approach at promoting neural recovery in adults and children with a variety of disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although some studies have challenged current practice patterns, families of infants born preterm are not routinely provided with information or recommendations on why and how to provide early experiences in the first months of life. 6,7,[12][13][14] Delaying intervention limits the amount of intervention provided during a critical window for altering neural pathways and likely reduces the efficacy of EI on motor development. 3,10,15 Supporting Play Exploration and Early Development Intervention (SPEEDI) is an intervention that blends the need for early and intense intervention with family support to engage families in their child's development during transition from the NICU to home and the community.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,17,20,21 NICU nurses and neonatologists have been reported to be the primary sources of this information, 19,20,22 but studies have also shown that parents may use other sources such as parent-to-parent support, written materials, and online information. 8,14,23 Learning style varies from person to person and includes visual, aural, read/write, and kinesthetic learning, each of which has to be addressed in the development of educational programs. 8,14,23 Learning style varies from person to person and includes visual, aural, read/write, and kinesthetic learning, each of which has to be addressed in the development of educational programs.…”
Section: Research Supporting the Design Of The Programmentioning
confidence: 99%
“…Dusing et al 23 Qualitative study of parents' preferred method of receiving educational material about their preterm infant.…”
Section: Teaching Approaches and Toolsmentioning
confidence: 99%
“…Ideally, parent educational materials must meet the informational needs of all families, the information must be easy to understand, and accessible outside the hospital for review and sharing. [4][5][6][7][8] Cognition science evidence shows that the combination of graphics and narration facilitates greater understanding of concepts and the visuals help with the neural storage and retrieval of information. 9 An added benefit in using multimedia is for low-literate adults, who focus on word-for-word reading in written text rather than comprehending key concepts.…”
Section: Introductionmentioning
confidence: 99%